2010
DOI: 10.1108/17590831011026240
|View full text |Cite
|
Sign up to set email alerts
|

Shariah observation: advertising practices of Bank Muamalat in Malaysia

Abstract: Purpose -The purpose of this paper is to assess the existing advertising practices in Malaysia and their compliance with the Shariah (Islamic Law). Design/methodology/approach -Using descriptive observations, the promotional tools and practices used by the prominent conventional banks were compared to those used by the Islamic banks. A total of 40 different advertisements were assessed as well as staff and personnel from 30 branches were interviewed. Findings -The paper reveals that customers remain unaware of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 20 publications
0
53
0
2
Order By: Relevance
“…Indeed, service quality is considered the primary factor in customer satisfaction with banks due to its impact on customer loyalty (Gait and Worthington, 2008). Perhaps as a direct result there has been a wide range of studies that have examined SERVQUAL in a banking context (see for example , Avkiran 1994;Haque, 2010;Mersha and Adlaka, 1992). The majority of studies have measured service quality by replicating or adapting the SERVQUAL model (e.g.…”
Section: Service Quality Banks and Islamic Banksmentioning
confidence: 99%
“…Indeed, service quality is considered the primary factor in customer satisfaction with banks due to its impact on customer loyalty (Gait and Worthington, 2008). Perhaps as a direct result there has been a wide range of studies that have examined SERVQUAL in a banking context (see for example , Avkiran 1994;Haque, 2010;Mersha and Adlaka, 1992). The majority of studies have measured service quality by replicating or adapting the SERVQUAL model (e.g.…”
Section: Service Quality Banks and Islamic Banksmentioning
confidence: 99%
“…A conservative estimates shows that Asia is home to an almost 700 million Muslims, some 60 per cent of the global total (O'Neill, 2010). Research has also shown that in countries such as Egypt, Iran, India, Malaysia, Morocco, Saudi Arabia and South Africa, Muslim consumers hold a great purchasing power (Haque, Ahmed & Jahan, 2010). The Islamic population has grown in size and affluence and as mentioned by Temporal (2011) there are 1.57 billion Muslims worldwide with more multinationals seeking to tap into the market.…”
Section: Introductionmentioning
confidence: 99%
“…Association of advertising and brands with particular religious symbol is likely to affect consumer attitude and behaviour towards the object. For example, advertising campaigns based on religious themes attract Muslim consumers and increase awareness about the product (Haque, Khaliq, & Jahan, 2010).…”
Section: Research Contextmentioning
confidence: 99%